Interpoziční a závěsná artroplastika kořenového kloubu palce ruky pomocí implantátu TIE-IN - Jurča, Jiří; Havlas, Vojtěch (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2018)
PURPOSE OF THE STUDY The aim of the study was to present the surgical technique combining the interposition and suspension arthroplasty using the TIE-IN implant as a treatment option for advanced symptomatic to final stage rhizarthrosis. MATERIAL AND METHODS Since 2015 we have performed the interposition arthroplasty combined with suspension arthroplasty using the TIE-IN implant in 12 patients, mostly indicated for stage IV rhizarthrosis. In two cases stage III rhizarthrosis with concomitant trapezium destruction was present. In two other cases the patients suffered from secondary osteoarthrosis associated with rheumatoid arthritis. Pain under loads was present in all the patients, of whom in 10 patients also the pain at rest occurred. Preoperatively, a total of 10 patients showed subluxation of the first carpometacarpal joint of 50% of the articular surface width. The ratio between the dominant and non-dominant extremity was 1:1. As a part of the evaluation, correlation was established between the preoperative findings and the postoperative results at 3 months follow-up. The examination included the assessment of pain intensity by VAS scale, the range of motion measurement - by Kapandji thumb opposition test, handgrip strength test and functional evaluation using the scoring systems - DASH score, modified DASH score for thumb, and modified Wrightington score. RESULTS No intraoperative or postoperative complications such as infection, complex regional pain syndrome, implant failure or failed surgical procedure were reported in the given group of patients. The pain at rest ceased in all 12 patients. The VAS pain intensity score improved from the preoperative average of 5.8 to 0.8 postoperatively. The range of motion in all the patients with stage IV rhizarthrosis substantially improved. The average Kapandji thumb opposition score increased from 6.9 preoperatively to 9.5 postoperatively. DISCUSSION There are multiple surgical treatment options for advanced rhizarthrosis. Apart from the combination of interposition and suspension arthroplasty referred to above, it is trapeziometacarpal (TMC) arthrodesis on the one hand and carpometacarpal joint total arthroplasty on the other hand. The arthrodesis continues to be a fairly frequently used procedure, despite the final limitation of thumb movement. It is because of this loss of fine motor function why it is not the preferred technique for treating advanced rhizarthrosis at our department. On the very contrary, the total replacement of the TMC joint is at our department as well as at many other departments the treatment of choice for advanced symptomatic rhizarthrosis since in conservative resection of the articular surfaces the biomechanics of the carpometacarpal joint of the thumb is preserved. As an outcome, this technique combines the advantages of other surgical methods by ensuring full painless range of motion and strength of the joint as opposed to other techniques, which mostly result either in a limited movement, or in a loss of grip strength. There is a whole range of resection arthroplasty techniques available. From simple trapeziectomy, which leads to the radial column collapse and ultimately to a major functional deficit, up to various interposition or suspension arthroplasty techniques with the resulting range of motion, stability and thus grip strength depending on the technique applied. CONCLUSIONS By applying the combination of the interposition and suspension arthroplasty of the carpometacarpal joint of the thumb using the TIE-IN implant we preserve the length of the thumb, its stability, and thus achieve the recovery of adequate thumb range of motion and grip strength. Our conclusions are in correlation with the results obtained at reference centres. Key words:rhizarthrosis, trapeziometacarpal prosthesis, arthroplasty, trapezium implant.
Keywords: síla ruky; Carpometacarpal Joints; Hand Strength; osteoartróza; Pain Measurement; palec ruky; Arthroplasty, Replacement; karpometakarpální klouby; artroplastiky kloubů; lidé; pooperační komplikace; Thumb; měření bolesti; Range of Motion, Articular; rozsah kloubních pohybů; Postoperative Complications; Trapezium Bone; Aged; Osteoarthritis; Joint Prosthesis; protézy kloubů; lidé středního věku; senioři; trapézová kost; Middle Aged; Humans